1991
DOI: 10.3109/10826089109053186
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Resumption of Drinking in Posttreatment Alcoholics

Abstract: The ability of five factors (depressive symptomatology, neuropsychological performance, psychosocial maladjustment, previous treatment history, and childhood attention deficit disorder symptomatology) to predict relapse was examined in a follow-up experimental design. Fifty-eight male and 45 female alcoholics were interviewed immediately following release from inpatient treatment units. Fourteen months later, 41 subjects (41%) were classified as resumers; 62 (59%) were abstainers. Resumers showed significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 33 publications
6
49
0
1
Order By: Relevance
“…With regard to the background variables, our results confirm those obtained in other studies (Finney & Moos, 1992;Glenn & Parsons, 1991). The relationship between these variables and abstinence is weak, when not nonexistent, and, since little can be done to modify these variables, the studies do not offer relevant information about treatment.…”
Section: Discussionsupporting
confidence: 80%
“…With regard to the background variables, our results confirm those obtained in other studies (Finney & Moos, 1992;Glenn & Parsons, 1991). The relationship between these variables and abstinence is weak, when not nonexistent, and, since little can be done to modify these variables, the studies do not offer relevant information about treatment.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, co-occurrence of alcoholism with neuropsychological disorders such as anxiety and/or depression, can introduce therapeutic challenges for treatment of alcoholism. This is most readily manifested in terms of relapse prevention as such mood disorders may significantly facilitate relapse to alcohol use (Glenn and Parsons, 1991;Driessen et al, 2001;De Witte et al, 2003;Saatcioglu et al, 2008). The results of current study, using an animal model, suggest that administration of an antidepressant can counteract anxiety-and depressive-like behavior induced by chronic alcohol administration.…”
Section: Discussionmentioning
confidence: 72%
“…These co-morbid conditions are manifested more in alcoholic women (50%) than men (30%) (U.S. Department of Health and Human Services, 1993;Kessler et al, 1994;Arolt and Driessen, 1996;Schuckit et al, 1997;Berglund and Ojehagen, 1998;Swendsen et al, 1998;Tondo et al, 1999) and are particularly high during and/or following alcohol withdrawal (Behar et al, 1984;Turnbull and Gomberg, 1988). Anxiety and depression are purported to result in an early and increased alcohol relapse risk (Glenn and Parsons, 1991;De Witte et al, 2003). Whereas the relapse rates for alcoholic patients without co-morbid disorders may be about 40%, these rates jump to about 69% or 77% for alcoholics with anxiety or the combination of anxiety and depressive disorders, respectively (Driessen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 30 baseline variables have been identified and clustered into sociodemographic, alcohol-related and clinical domains [19,20]. Some studies have reported that certain variables that are commonly used as primary outcomes may have predictive value, including baseline alcohol consumption [21][22][23][24], dependence severity [24][25][26][27] and history of previous treatment or intervention [23,[28][29][30]. Only one such study has investigated whether relapse can be predicted by measuring baseline QOL, using the Life Situation Survey (LSS) in a small sample of alcohol-dependent patients, but this approach failed to identify any significant predictors [4].…”
Section: Introductionmentioning
confidence: 99%